“АЛПОМИШ” ДОСТОНИДА ҚЎЛЛАНИЛГАН ЎХШАТИШЛАРНИНГ ЛИНГВОКУЛЬТУРОЛОГИК ХУСУСИЯТЛАРИ (Scientific journal of the Fergana State University, 2023)
This article analyses the classification of  simile into groups and  national  outlook which reflected in  simile, divided into meaningful groups, the attitudes to nature and society,  national think of world cognition, comparing skill to nature and